A Na2CO3-Responsive Chitinase Gene From Leymus chinensis Improve Pathogen Resistance and Saline-Alkali Stress Tolerance in Transgenic Tobacco and Maize - Liu, Xiangguo; Yu, Ying; Liu, Qing; Deng, Suren; Jin, Xuebo; Yin, Yuejia; Guo, Jia; Li, Nan; Liu, Yang; Han, Siping; Wang, Chuang; Hao, Dongyun (Frontiers in Plant Science, 2020)
Salinity and microbial pathogens are the major limiting factors for crop production. Although the manipulation of many genes could improve plant performance under either of these stresses, few genes have reported that could improve both pathogen resistance and saline-alkali stress tolerance. In this study, we identified a new chitinase gene CHITINASE 2 (LcCHI2) that encodes a class II chitinase from Leymus chinensis, which grows naturally on alkaline-sodic soil. Overexpression of LcCHI2 increased chitinase activity in transgenic plants. The transgenic tobacco and maize exhibited improved pathogen resistance and enhanced both neutral salt and alkaline salt stress tolerance. Overexpression of LcCHI2 reduced sodium (Na+) accumulation, malondialdehyde content and relative electrical conductivity in transgenic tobacco under salt stress. In addition, the transgenic tobacco showed diminished lesion against bacterial and fungal pathogen challenge, suggesting an improved disease resistance. Similar improved performance was also observed in LcCHI2-overexpressed maize under both pathogen and salt stresses. It is worth noting that this genetic manipulation does not impair the growth and yield of transgenic tobacco and maize under normal cultivation condition. Apparently, application of LcCHI2 provides a new train of thought for genetically engineering saline-alkali and pathogen resistant crops of both dicots and monocots.